Eosinophilic esophagitis: clinical features, endoscopic findings and response to treatment - U. D., Manoranjan; S., Nikhil; M. N., Divyarani; N. T., Akhila (International Surgery Journal, 2018)
Background: Eosinophilic esophagitis (EoE) considered to be an allergic inflammatory disorder of the esophagus characterised by an inherent impairment in epithelial barrier integrity, possibly worsened by reflux of gastric contents. The aim of this study was to study EoE and its clinical and endoscopic evaluation and response to treatment with relapse rates. Methods: Fifty patients in the study were selected based on a review of biopsy results from previous endoscopies performed between August 2015 to August 2017. All patients with biopsy-proven EoE, defined as more than 20 eosinophils/HPF. Biopsy samples were taken from the mid and distal esophagus and sent for analysis. The endoscopic findings were noted grossly. Twenty five patients were started on PPI’s only and the remaining 25 patients were started on fluticasone MDI 440mcg inhaled two times day and PPI. Follow up of the patients was done at 1, 3 and 6 months after treatment. Results: The mean age in the study population was 42 years, males affected more often (64%) with rings and corrugations and linear furrows being the most commonly seen endoscopic findings (64% and 27%). Normal study was seen in 40% of the patients. Most common symptom was dysphagia 26%. Steroids are the mainstay of the treatment along with PPI. Relapse rate was 61.1% in the study. Conclusions: EoE is an inflammatory condition of the oesophagus that occurs predominantly in young and middle-aged men, EE should be strongly considered in those who present with dysphagia and/or food impaction, particularly with a history of atopic disorders. Swallowed fluticasone is a safe and effective treatment; however, relapse rates are very high. In adults, there remains a need for a randomized controlled trial to assess the safety and efficacy of various treatment modalities.